Effect of Fiber Angles on Hybrid Double-Tube Concrete Columns under Monotonic Axial Compression - Bing Zhang; Yu-Jun Qi; Tao Huang; Qian-Biao Zhang; Yu Hu; Xia-Min Hu (Advances in Civil Engineering)
Hybrid double-tube concrete columns (hybrid DTCCs) are a novel form of hybrid columns that combine fiber-reinforced polymer (FRP) composites with two traditional construction materials (i.e., concrete and steel). Hybrid DTCCs consist of an outer FRP tube and an inner steel tube aligned concentrically, with the space between the two tubes and inside of the steel tube filled with concrete. The three materials (i.e., FRP, concrete, and steel) in hybrid DTCCs are combined optimally to deliver excellent performances, such as excellent ductility and remarkable corrosion resistance. Recently, hybrid DTCCs have received increasing research attention on their compressive behavior. Existing studies, however, are focused on hybrid DTCCs with fibers of the FRP tube oriented in the hoop direction or close to the hoop direction. Against this background, this paper presents a series of monotonic axial compression tests on hybrid DTCCs with a particular focus on the effect of fiber angles (i.e., the angle of the fiber orientations to the longitudinal axis of the FRP tube). Three types of fiber angles (i.e., ±45°, ±60°, or ±80°) and two FRP tube thicknesses (i.e., 4 mm and 8 mm) were employed in the present study. Experimental results show that the concrete in hybrid DTCCs is well confined by both the FRP tube and the steel tube, leading to excellent ductility; the confinement effect of the FRP tube increases with the increase of the absolute value of fiber angles, whereas the ultimate axial strain decreases with the increase of the absolute value of fiber angles. An existing analysis-oriented model, which considers the different confining states of the concrete between the two tubes and that inside of the steel tube, is verified using the present test results. The model is capable of providing accurate predictions for hybrid DTCCs with a ±80° FRP tube. For hybrid DTCCs with a ±45° or ±60° FRP tube, the model yields reasonable accurate predictions for the peak axial load but underestimates the ultimate axial strain consistently.